ANALYSIS OF OCCUPATIONAL STRESS ON NURSES IN TOTO KABILA REGIONAL GENERAL HOSPITAL - Ayu Rofia Nurfadillah; Nur Ayini S. Lalu (UNG, 2022)
Nursing is a very stressful job because a nursing service provider has a longer duration with patients and is required to provide quality services quickly, precisely, and carefully in complex circumstances or conditions. In addition, nurses are often burdened with other additional tasks and often carry out activities that are not their functions, such as handling administration, finance, and others. Nurses have higher stress levels than other professionals in hospitals. The novelty of this study is because it examines work stress on nurses at TOTO KABILA Hospital. The purpose of this study was to analyze work stress on nurses at Toto Kabila Hospital. The research design used a cross-sectional design, with a research sample of 116 nurses. Analysis of the data used is the chi-square test. The results showed that nurses who had a less heavy workload and experienced moderate work stress were 17 respondents (54.8%) and those who experienced severe work stress were 14 respondents (45.2%). At the same time, nurses with a heavy workload and moderate work stress are 22 respondents (25.9%), and among experts with serious work stress, as many as 63 respondents (74.1%). For good interpersonal relationships, 2 respondents (9.1%) experienced work stress, and 20 respondents (90.9%). Meanwhile, interpersonal relationships that experienced moderate work stress were 37 respondents (39.4%), and severe work stresses 57 respondents (60.6%). The conclusion is that there is a relationship between the workload and interpersonal relationships of nurses with the work stress of nurses at Toto Kabila Hospital, with a value of 0.05. Suggestions are expected that the nurses of RSUD Toto Kabila can manage their working time well, use time effectively in order to complete their work on time, and can find the best solution for every problem faced so as to reduce the workload that results in work stress.